Optimasi Masker Gel Peel-Off Ekstrak Etanolik Daun Sirih (Piper Betle L.) dengan Kombinasi Carbomer dan Polivinil Alkohol - Gunawan Setiyadi; Annisa Qonitah (Pharmacon: Jurnal Farmasi Indonesia, 2020)
Betel leaf (Piper betle L.) is a plant that has potential as a source of natural antioxidants. The purpose of this study was to determine the effect of the combination of carbomer and PVA on the homogeneity, dispersibility, adhesion, viscosity, dry time, elasticity and pH of the gel peel-off mask preparation; obtain the optimum formula and determine the antioxidant activity of the optimum formula. Extraction of betel leaf was carried out using the maceration method with 96% ethanol as a solvent. The experimental design was made using Design Expert software version 11 with the Simplex Lattice Design (SLD) method with the optimized components being carbomer and PVA. The response of physical properties in the form of spreadability, adhesion, pH, viscosity, dry time, and elasticity of each formula is measured and the measurement data is processed with Design Expert software to determine the optimum formula based on predetermined criteria. The verification dosage form is made based on the optimum formula composition produced. The response of the optimum physical properties of the prediction formula was compared with the results of the verification preparation with the One sample t-test. The yield of thick betel leaf extract in this study was 20.26%. The optimum formula has homogeneous characteristics with a distinctive odor of dark green betel leaf and semi-solid form, spreadability 49.25 ± 0.29 cm2, adhesion 4.77 ± 0.22 seconds, pH 7.26 ± 0.119, viscosity 763 ± 12.47 dPas, drying time 29.68 ± 0.52 minutes, elasticity 1.05 ± 0.04%. The antioxidant activity of betel leaf ethanolic extract has an IC50 value of 7.62 µg / mL and the optimum formula has an IC50 value of 111.25 µg / mL.